The swine intestinal wall thickening dynamic in result of different pressure applying inside the welding anastomotic instrument model - S. S. Podpriatov; S. E. Podpriatov; G. S. Marinsky; V. A. Tkachenko; V. G. Hetman; K. G. Lopatkina (Kazimierz Wielki University, 2018)
Introduction. The life-time studies of intestine operate at a pressure of 0.003-0.006 (N/m2). To create magnetic ring anastomosis 0.1-0.4 N/m2 pressure is used. The right initial compression of intestine walls before radio frequency electric influence isn't established properly, but obviously has to homogenize the tissues dense. Several publications according 1.125 N/mm2 pressure was found. Aim to investigate the thinning dynamics of intestinal walls having human-sized dimensions during the high pressure action, in attempt to determine the optimal moment of anastomotic welding beginning. Material and methods. The swine organ complex was delivered to laboratory during 6 hours at 4 оС, and then was heated to 28-32 оС into 0.9% NaCl. Two intestine walls having human sizes were positioned on electrodes inside the anastomotic device prototype. After fixation, tissues were pressed for 60 or 120 seconds. The 30 experiments were provided using pressure values 2.1, 3.0, 3.9 and 5.0 N/mm2 for tissues thinning dynamic investigation by connected to electrodes micrometer device. Results and discussion. The thinning of two intestinal walls, occurs as result of applied by electrodes external pressure, valued in range from 2.1 or 3.9 N/mm2, significantly reduces it's tempo from 35th to 60th action sec. We allow that this resistance derives from the mucous and submucosal layers. Under a pressure of 1.1 N/mm2, the similar thickness degree and tempo is achieved by pressure prolongation to 120 sec, but under 5.0 N/mm2 it needs 20 sec. The pressure by 3.0-3.9 N/mm2 over 35 sec, or 5.0 N/mm2 over 20 sec are resulted in much lower tissue stabilizing level. Obviously, its structural ground is a resistance combination of all intestinal layers at the crash edge. Conclusions. By choosing the appropriate pressure value from 1.1 to 5.0 N/mm2 and its exposure time from 20 to 120 seconds, it is possible to adjust the degree of tissue dense before the subsequent connection.